HU-Model Effectiveness in Corruption Detection - Umar, Haryono; Safaria, Siti; Mudiar, Welda; Purba, Rahima Br; Harsono, Harsono; Karyaningsih, Karyaningsih (Budapest International Research and Critics University, 2021)
This study aims to test the effectiveness of the HU-Model used in corruption detection efforts. The increasing number of corruption cases shows that the tools to detect corruption are not yet available. With the mode of corruption that is increasingly developing and complex, the existence of a corruption detection tool is a must. The focus of this research is on the causes of fraud star corruption which shows that the cause is due to abuse of power or the authority being exercised is not by the mandate. The characteristics of corruption in Indonesia are very complex, involving various elements from the government / private sector, State / Regional Owned Enterprises (BUMN / D) as well as public officials from the center to the regions. This article discusses the corruption detection model as one of the contributions to fight corruption in Indonesia. As one of the efforts to make Indonesia free from corruption outbreaks, the HU model consists of the variable lack of integrity (lack of integrity), opportunity (opportunity), pressure (pressure), rationalization (rationalization), and the ability (capability) to provide hope and answers. The HU-Model proves that despite the amount of pressure, the number of opportunities, the ease of justification, and the high position and authority will not encourage acts of corruption if there is still strong integrity. The results show that the indications of corruption are divided into three clusters, namely those with indications of corruption (red), gray (gray), and no indications of corruption (green).